Kampanye Sosial Red Readerhood 2019 Untuk Meningkatkan Minat Baca Anak - Sari, Diah Kencana (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2019)
Big Bad Wolf Book Sale was first held in Kuala Lumpur, Malaysia, in 2009. seven years later, The Ministry of Culture and Education worked together with PT Jaya Ritel Indonesia to hold Big Bad Wolf Book Sale in Jakarta. Putting forward its vision and mission which is "Read to Enlight Nation", the book sale comes back in 2019 with its social campaign program known as "Red Readerhood". The purpose of the social campaign is to raise literacy by encouraging people to donate books within the sale event. This social campaign program employs Ronald D. Smith's 9 Steps of Strategic Planning to.The Social Campaign Program Red Readerhood as a part of Big Bad Wolf Book Sale consists of three main sub-events: (1) pre-event; (2) event, and (3) post-event. School visitation in the Jabodetabek area involving story-tellers and press conference is the pre-event phase. The phase then continues with Red Readerhood Charity, Partnership, and competitions such as storytelling and Blogger & Vlogger competition. the post-event phase includes Book Charity Report, Radio Interview and Youtube Video ContentÂ